2018
DOI: 10.7717/peerj.5722
|View full text |Cite
|
Sign up to set email alerts
|

In search of an optimum sampling algorithm for prediction of soil properties from infrared spectra

Abstract: BackgroundThe use of visible-near infrared (vis-NIR) spectroscopy for rapid soil characterisation has gained a lot of interest in recent times. Soil spectra absorbance from the visible-infrared range can be calibrated using regression models to predict a set of soil properties. The accuracy of these regression models relies heavily on the calibration set. The optimum sample size and the overall sample representativeness of the dataset could further improve the model performance. However, there is no guideline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
1
24
1
1
Order By: Relevance
“…Better generalisation can be made by training the model in a larger data set. However, several studies demonstrated that the performance of the machine learning model did not increase significantly, or it even plateaued, as the calibration sample size increased (Figueroa et al, 2012;Ramirez-Lopez et al, 2014;Ng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Better generalisation can be made by training the model in a larger data set. However, several studies demonstrated that the performance of the machine learning model did not increase significantly, or it even plateaued, as the calibration sample size increased (Figueroa et al, 2012;Ramirez-Lopez et al, 2014;Ng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near infrared spectroscopy has been shown to successfully estimate various soil properties in many studies (e.g. Ng, Minasny, Malone, & Filippi, ; Singh et al, ; Stenberg, Rossel, Mouazen, & Wetterlind, ). The fundamental of soil reflectance spectroscopy is the stretching or bending of molecular bond that causes vibration to various degrees after absorbing light.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the soil variability in the calibration dataset to only reflect the variability that will be encountered in the pilot study area would most likely improve predictions (Viscarra-Rossel et al, 2008). Also, we used a large sample size in our calibrations (on average n = 668; Supplemental Table S1), which may have created more reliable and representative models compared with models based on smaller datasets for similar-size geographical areas (Ng et al, 2018).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%